ANALISIS FAKTOR-FAKTOR PENGAMBILAN KEPUTUSAN MAHASISWA MEMILIH STIE “AMA” SALATIGA - Purwanto, Endang (AMONG MAKARTI, 2015)
AbstractEducation has a very central and strategic position, if it is associated with improved quality of Human Resources. Under these conditions, student's decision making process in choosing a particular private college is very important to be known by the manager of the college through the study of consumer behavior. There are several factors that influence consumer behavior, namely cultural, social, personal, and psychological. There are five stages of decision-making process, starting from problem recognition, information search, evaluation of alternatives, purchase decision, and post-purchase behavior. This study uses a survey with a questionnaire as a data collection tool and using the Cochran test to test the significance of each of the factors that influence the decision of students choosing STIE AMA Salatiga.  Results of the data analysis showed that the students decide to choose STIE AMA Salatiga due to the existing courses namely the Diploma III and Bachelor programs (Undergraduate/S1), the accessible location, tuition fee affordability, the services provided to students, and a sense of pride to become a higher school student.The research results suggest that the manager should still be able to maintain the five factors that into consideration of student's decision to choose STIE AMA Salatiga, because these five factors become the strength to compete with other colleges.  Keywords: Decision making, students, STIE AMA Salatiga